Autonomous fiber-optic gas monitoring system with thermoelectric power supply - Nowrot, Andrzej; Świderska-Środa, Anna; Łojkowski, Witold; Żur, Krzysztof Kamil; Mikołajczyk, Monika (Wydawnictwa AGH, 2017)
This paper presents the concept of an autonomous measuring instrument powered by a locally accessible source of heat with a contact surface area of over a dozen or several dozen square centimeters and a temperature higher or lower than the ambient temperature. The design and construction of the measuring device will be based on two modules developed and constructed in the course of previous work: a dedicated low-power thermoelectric generator and luminescent fiber-optic detector. The system can be additional equipped with a wireless transmission module. The studies show that, due to the power supply and photoluminescent measurement system with high stability of the operating point, this device will be capable of continuous operation without maintenance for many months.
Autonomiczny światłowodowy układ monitorowania stężenia gazów z zasilaniem termoelektrycznym
Mining - Informatics, Automation and Electrical Engineering
Bibliogr. s. 11-12.
Keywords: gasometry; thermocouple; nanotechnology